Gambaran Kecenderungan Orthorexia Nervosa pada Mahasiswa Program Studi Kedokteran FK-KMK UGM - Mutiara Anisha Zahra; Irwan Supriyanto; Sri Warsini (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2021)
Background: Orthorexia nervosa (ON) is a new psychological disorder that still needs further research. People living with ON have unsafe obsession with eating healthy food. Research related to ON among graduate students in Indonesia, especially medical students, has not been done.Research Objectives: This study aims to determine the proportion of orthorexia nervosa (ON) tendency and to investigate certain characteristics that might influence ON tendency among medical students at FK-KMK UGM.Methodology: This research was a descriptive study with a cross-sectional design. Data collection took place in October-November 2019. Respondents involved were 97 students. The instrument used was ORTO-15. The results were analysed with Chi-Square Test and Fisher Test.Results: The proportion of ON tendency among respondents was 44.3% (cut-off point 40) and there were significant relationship between ON tendency with the habit of respondents to access health related articles in web pages and social media.Conclusion: The ON tendency among medical students in FK-KMK UGM is relatively high with a prevalence percentage of 44.3%. Prevention efforts need to be made so that this trend does not develop into an actual health problem. ABSTRAKLatar Belakang: Orthorexia nervosa (ON) merupakan gangguan psikologis baru yang masih perlu banyak diteliti dengan ciri-ciri penderita memiliki obsesi berlebih terhadap pola makan yang dianggap sehat. Hingga saat ini penelitian terkait ON pada mahasiswa di Indonesia, khususnya mahasiswa kedokteran belum dilakukan.Tujuan Penelitian: Penelitian ini bertujuan untuk mengetahui proporsi kecenderungan orthorexia nervosa (ON) dan karakteristik responden yang memengaruhi kecenderungan ON pada mahasiswa Prodi Kedokteran FK-KMK UGM.Metodologi: Penelitian ini adalah penelitian deskriptif dengan desain cross-sectional. Pengambilan data berlangsung pada bulan Oktober-November tahun 2019. Responden yang terlibat sebanyak 97 mahasiswa. Instrumen yang digunakan adalah ORTO-15. Hasil analisa dilakukan dengan Chi-square dan Fisher test.Hasil: Proporsi kecenderungan ON pada responden adalah 44,3% (cut-off point 40). Ditemukan hubungan signifikan antara kecenderungan ON dengan kegemaran responden untuk mengakses laman berkaitan dengan kesehatan di sosial media (p<0,05).Kesimpulan:  Kecenderungan ON pada mahasiswa kedokteran FK-KMK UGM tergolong tinggi. Perlu dilakukan upaya pencegahan agar kecenderungan ini tidak berkembang menjadi masalah kesehatan yang aktual.